State size as measured in terms of public spending and world health, 1990-2000 Tamaño del Estado [gasto público] y salud en el mundo, 1990-2000 - Álvaro Franco; Diana Gil; Carlos Álvarez-Dardet (Elsevier, 2005)
Objective: To determine the relationship between state size (measured in terms of public spending) and public health indicators in a sample of countries representing all regions of the world and from 1990-2000. Methods: An ecological study was performed using data on Central Government Spending (CGS) and per capita Gross National Product (GNP) obtained from the International Monetary Fund, and on life expectancy, maternal, and infant mortality, provided by the World Health Organization. A multiple linear regression model was fitted to estimate the effect of CGS on health, which also took into consideration per capita GNP and geographical region. Results: CGS varied little over the study period, with convergence around an average of 28%, but within a relatively wide range (7.80-53.0%); the countries with the strongest economies (according to per capita GNP) had the highest levels of CGS. The influence of this factor was particularly relevant for the infant mortality rate (r = 0.40; beta = -1.327; EE = 0.237; t = -5.590; p < 0.001). Per capita GNP and geographic location were also associated with variations in health; health indicators tended to be worse for poorer countries in Africa and Asia. In the adjusted model, CGS was statistically significant with regard to infant and maternal mortality rates. Conclusion: The study suggests that state size (in terms of public spending) has an important influence upon health and particularly upon mortality. Although it is important to bear in mind the limitations of this study and the reduced time window used, these results should be taken into consideration in the current political and epidemiological debate. Objetivo: Determinar la relación entre el tamaño del Estado (medido como el gasto público) y los indicadores de salud en una muestra de países de todas las regiones del mundo, en la década de los noventa. Métodos: Se realizó un estudio ecológico a partir de datos sobre gasto gubernamental central (GGC) y producto interior bruto (PIB) per cápita, obtenidos del Fondo Monetario Internacional, y de esperanza de vida, mortalidad materna y mortalidad infantil, de la Organización Mundial de la Salud. Se construyó un modelo de regresión lineal múltiple, para estimar el efecto del GGC sobre salud, y se introdujo también PIB per cápita y región. Resultados: El GGC varía poco durante el período estudiado, convergiendo alrededor de una media del 28%, pero aún dentro de un amplio rango (7,80-53,0%); los países con economías altas (según PIB per cápita) presentan mayor GGC. Su efecto tiene especial importancia sobre la mortalidad infantil (r = 0,40; beta = -1,327; EE = 0,237; t = -5,590; p < 0,001). También el PIB per cápita y la ubicación regional se asocian a los cambios en salud, coincidiendo con el empeoramiento de los indicadores de salud en algunos países pobres de África y Asia. En el modelo ajustado, el GGC mantiene la asociación estadística con mortalidad infantil y mortalidad materna. Conclusión: El estudio sugiere un efecto importante del tamaño del Estado sobre la situación de salud, específicamente sobre la mortalidad. Aunque tienen limitaciones, dada la reducida ventana temporal utilizada, estos resultados deben ser considerados en el debate político y epidemiológico actual.